A computerised calibration service supporting system. II: A web interface design. (29th October 2004) - Liu, Thu-Hua; Hwang, Sheue-Ling; Wang, Jia-Ching
This research combines information technology in the Standard of Exchange Product model data (STEP) and Internet communication by constructing a user interface for object-oriented database management system on a world wide web (WWW) server. To construct the user interface, we chose an enterprise as our case system. Then, we analysed the workflow of the case company and the interface of its database. The database interface was then transferred from a DOS system to a Web system. Finally, the new system was tested and evaluated. It is shown that the regular business processes can be integrated through Internet communications, but some limitations still exist. In addition, some comments and the guidelines for designing the user WWW interface are documented for designers to refer to.